Oral Sex, Young People, and Gendered Narratives of Reciprocity. Issue 7 (1st September 2016) - Lewis, Ruth; Marston, Cicely
Abstract : Young people in many countries report gender differences in giving and receiving oral sex, yet examination of young people's own perspectives on gender dynamics in oral heterosex are relatively rare. We explored the constructs and discourses 16- to 18-year-old men and women in England used in their accounts of oral sex during in-depth interviews. Two contrasting constructs were in circulation in the accounts: on one hand, oral sex on men and women was narrated as equivalent, while on the other, oral sex on women was seen as "a bigger deal" than oral sex on men. Young men and women used a "give and take" discourse, which constructed the mutual exchange of oral sex as "fair." Appeals to an ethic of reciprocity in oral sex enabled women to present themselves as demanding equality in their sexual interactions, and men as supporting mutuality. However, we show how these ostensibly positive discourses about equality also worked in narratives to obscure women's constrained agency and work with respect to giving oral sex.